Descripción de la construcción del convertidor binario-decimal como recurso educativo para la enseñanza del sistema de numeración binario en el primer año de bachillerato Técnico en informática en la Unidad Educativa Emiliano Ortega Espinoza del cantón Catamayo durante el año lectivo 2022-2023. - Acaro Pinta, Henry Javier (2023)
The educational resources developed by teachers and students for a given educational context strengthen the problem skills, collaborative work, creativity, and decision to making, as well as promote dynamic and interdisciplinary teaching, thus allowing students to acquire knowledge through active learning. In this sense, this research describes the construction of the digital converter as an educational resource for teaching the binary number system, it is an exploration and descriptive study, the curricular contents provided by the Ministry of Education for the area of computer science were used as a research instrument, while the methodology was based on the research and development approach, where in the first stage the theoretical references that support the construction of the binary-decimal converter were investigated, The second stage describes the construction of the resource through the instructional design model Analysis, Design, Development, Implementation and Evaluation (ADDIE), where a roadmap was generated so that the resource, through the elements that comprise it, can be reprogrammed to be replicated or adapted to another educational context. To concluded that, describing the construction of the binary-decimal converter as an educational resource demonstrates that an educational hardware can be created from scratch without the need to generate large production costs and that it responds to the learning objectives proposed by the Ecuadorian educational curriculum and especially to the educational needs of the students. It also shows the importance of working with an instructional methodology such as ADDIE to structure the development process, since each of its phases is governed by the fulfillment of the objectives set, to generate a quality product. Keywords: Binary-decimal converter; educational resource; ADDIE; education; innovation.